Keep/Refer-Decision-Making Abilities and Screening for Serious Pathologies as Integral Components of Physiotherapy Education and Profession - Lackenbauer, Wolfgang; Jansen, Jessie; Roddam, Hazel; Selfe, James (physioscience, 2019)
Background Several surveys over the last few years examined physiotherapists’ attitude towards direct access, increased practice autonomy and the necessity to detect the presence of serious pathologies.Objective The aim of the questionnaire was identify the attitude of Austrian physicians towards physiotherapists’ taking more responsibility in the case of clinical decisions.Method An online survey was distributed by e-mail among 1000 general practitioners and 395 orthopaedic surgeons working in private practice in Austria during autumn 2017.Results The study included 76 general practitioners (7.6 %) and 40 orthopaedic surgeons (10 %). 90 % of the responding general practitioners and 68 % of the orthopaedic surgeons believed that Austrian physiotherapists should be able to decide whether physiotherapy is indicated or not.Conclusion The majority of the study participants were in favour of Austrian physiotherapists taking more responsibility and that they independently decide about physiotherapeutic indication.
Keywords: clinical decisions; survey; physiotherapy; physicians